SEMANTIC-STYLISTIC PARADIGMS OF RELATED VERBS - Gaukhar Serikbaevna Xaldarchaeva (American Journals, 2022)
This article discusses the semantic-stylistic paradigms of related verbs in related and non-related languages, the linking verb device and it’s derivatives in the form of grammatical, lexical and syntactic means of expression.It is known that the English language is going through the process of simplification, which is observed in all languages, that is developing from an advanced synthesis to an analytical one. In this process, the role of connectives in general, including linking verbs, is increasing.
Keywords: semantic-stylistic paradigms, linking verbs, linguistic structure